Aksi mahasiswa menuju gerbang reformasi / A. Aruiobimo Nusantara, R. Masri Sareb Putra, J.B. Sudarmanto - Nusantara A. Ariobimo; Putra, Masri Sareb; Sudarmanto, YB (Grasindo, 1998)
xxv, 109 hlm. ilus. 18 cm.